Improving Students' English Competence through TOEFL Preparation Program for Vocational College Students - Damar Isti Pratiwi; Andesvan Gumay; Dimas Adi Perwira; Kiki Juli Anggoro (Abdimas Awang Long, 2026)
Global growth necessitates that students achieve proficiency in English as a requisite competency for graduation. Proficiency in English must be demonstrated with a certificate, such as a TOEFL certificate, with a minimum needed score. This prerequisite was problematic for non-English major students, as they had only studied English in the initial semester. Nonetheless, the requirement was in the last semester. Consequently, a community service program in the form of a TOEFL preparation program was essential for equipping students with the requisite English abilities to achieve a passing score. Following the dissemination of the data, the participants in this activity comprised 228 third-grade students from a vocational university in Indonesia. The program comprised two weeks and included a pretest, an introduction, training (including listening comprehension, structure and written expression, and reading comprehension), a posttest, and a survey. The activity’s findings indicated that the program improved students’ TOEFL scores relative to their original scores. However, a number of students have failed to meet the minimum required score. It is recommended that the community service program be conducted periodically to aid students in enhancing their English skills.